Агресивність засуджених-рецидивістів - Філоненко, В. М.; Filonenko, V. M. (Вісник Національного університету оборони України. - 2013. - Вип. 2(33). - С. 301-304, 2013)
Стаття присвячена вивченню агресивності злочинців-рецидивістів. Визначено загальний рівень агресивності засуджених, що відбувають покарання за скоєння корисливих і насильницьких злочинів. Проведено порівняння величин агресивності засуджених обох груп, вказані види агресивності, за якими спостерігається найбільша розбіжність.

The current paper studies aggression of reconvicted criminals. Defines aggression degree of reconvicted persons, who served time sentence for profit motive and violent crimes. The analysis of the data revealed that violent type criminals demonstrated more willingness to instances of outright aggression in behavior than profit motive criminals. They are inherent hostility, aggressiveness and vindictiveness in relation to society. Profit motive criminals are more likely to indirect aggression, suspicion and willingness to adapt to the environment. They are more mobile, active, want to consolidate their place and position in social relations, avoiding direct conflicts and clashes. Aggressive behavior of prisoners conditioned by their way of life before a conviction, thelevel of interaction in the microenvironment in places of confinement, their own moral and volitional qualities and orientation of personality.

Статья посвящена изучению агрессивности преступников-рецидивистов. Определена степень агрессивности осужденных, которые отбывают наказание за совершение корыстных и насильственных преступлений. Проведено сравнение уровней агрессивности осужденных обеих групп, указаны виды агрессивности, по которыми наблюдается наибольшее расхождение.
Keywords: агресивність; злочинці; рецидивісти; aggression; criminals; reconvicted persons; агрессивность; преступники; рецидивисты